2019
DOI: 10.2478/s11686-019-00098-w
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalences of Rickettsia conorii, Ehrlichia canis and Coxiella burnetii in Dogs from Montenegro

Abstract: Due to an unfortunate error during the processing of the article, the given name and family name of all authors were interchanged. The original article has been corrected.Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
8
0
2
Order By: Relevance
“…Interestingly, in 2012, a higher antibody positivity (8.0%) was found in dogs with owner comparing with those from the municipal kennel (4.6%) (data not shown). These findings are discordant with those obtained in Montenegro where a higher positivity was obtained in shelter dogs [37]. Additionally, in the United States, California, a higher positivity was observed in stray dogs than in dogs with owner [28].…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, in 2012, a higher antibody positivity (8.0%) was found in dogs with owner comparing with those from the municipal kennel (4.6%) (data not shown). These findings are discordant with those obtained in Montenegro where a higher positivity was obtained in shelter dogs [37]. Additionally, in the United States, California, a higher positivity was observed in stray dogs than in dogs with owner [28].…”
Section: Discussionsupporting
confidence: 68%
“…This VBP has been previously identified in 38.6% of red foxes from BiH (Hodžić et al., 2015) and less commonly by molecular means in dogs sampled in Serbia and Croatia (Gabrielli et al., 2015; Vojta et al., 2009). Unexpectedly, pathogens vectored by Rhipicephalus sanguineus sensu lato, such as A. platys and H. canis , were detected in dog population herein examined but not E. canis , despite its presence in dogs from neighbouring countries such as Montenegro (Laušević et al., 2019).…”
Section: Discussionmentioning
confidence: 79%
“…Other canine VBPs that are prevalent in this country include the Oriental eyeworm Thelazia callipaeda , a zoonotic nematode parasite implicated in occasional human infections in Eastern Europe (Colella et al., 2016; Hodžić et al., 2014; Paradžik et al., 2016), and the apicomplexan pathogen Hepatozoon canis (Hodžić et al., 2015). However, there have been no reports to date of bacterial VBPs infecting Bosnian canines, likely due to a dearth of research given that evidence of such pathogens has been found in neighboring countries (Huber et al., 2017; Laušević et al., 2019). In addition, rickettsial pathogens have been molecularly detected in Bosnian ticks, including the zoonotic bacterial species Anaplasma phagocytophilum (Hodžić et al., 2017), the causative agent of potentially lethal human granulocytic anaplasmosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ixodidae ailesine bağlı keneler insan ve hayvan sağlığını etkileyen çok sayıda hastalık etkenine vektörlük yapma potansiyeline sahiptirler (Yücesan et al, 2019). Bu etkenler arasında zoonotik önemi olan Coxiella burnetii (Cikman et al, 2017) ve son zamanlarda zoonoz olduğu düşünülen Ehrlichia canis (Laušević et al, 2019) bakterileri de yer almaktadır.…”
Section: Discussionunclassified
“…E. canis'in daha önce sadece köpekleri enfekte ettiği düşünülüyordu ancak, Venezuela'da bir grup asemptomatik insandan da izole edilip moleküler olarak tanımlanmıştır. Böylece E. canis, insanlar için de klinik hastalıkların potansiyel bir ajanı olarak düşünülmüştür (Laušević et al, 2019). E. canis, Akdeniz'e kıyısı olan tüm Avrupa ülkelerinde endemiktir (Santoro et al, 2016).…”
Section: Introductionunclassified